PSYCHOLOGICAL MORBIDITY AND IMPLICATIONS FOR THE RECOVERY OF ADULTS AFTER ONCOLOGY SURGERY - Luciana Regina Ferreira da Mata; Ana Cláudia da Cunha; Cristiane de Souza Lima Ziviani; Túlio Gonçalves da Fonseca; Mariana Ferreira Vaz Gontijo Bernardes; Patrícia Peres de Oliveira (Universidade Federal do Paraná, 2018)
Objective: to assess the construct of psychological morbidity (anxiety/depression) in adults in the postoperative period after oncology surgery, as well as its possible relationship with surgical recovery. Method: Correlational study with 96 adults who underwent oncology surgery admitted to a large hospital of the state of Minas Gerais, between August and December 2015, through the administration of a sociodemographic questionnaire, the Hospital Anxiety and Depression Scale and the Quality of Recovery Score, to assess surgical recovery. Descriptive analysis of data and Shapiro-Wilk, Mann-Whitney and Student's t-Test, as well as Pearson's and Spearman correlation coefficients were used. Results: the variables anxiety and depression had a negative relationship with surgical recovery. There was a negative relationship between the variables anxiety and age. Fifty nine (61.5%) participants showed anxiety symptoms and 38 (39.6%) had depression. The variables anxiety and schooling showed a positive relationship. Conclusion: Psychological morbidity was related to the quality of surgical recovery. Therefore, the planning of perioperative nursing actions is essential.